AAPPLICATION OF INNOVATIVE LEARNING IN THE 21ST CENTURY AT SD NEGERI 42 PEKANBARU: PENERAPAN PEMBELAJARAN INOVATIF ABAD 21 DI SD NEGERI 42 PEKANBARU - Marsela Aznur; Dea Mustika (SOSIOEDUKASI, 2026)
Innovative learning in the 21st century requires teachers to be able to integrate critical thinking skills, creativity, collaboration, communication, and the use of technology into the learning process. This study aims to describe the application of 21st century innovative learning in SD Negeri 42 Pekanbaru, including the strategies used by teachers, obstacles faced, and learning optimization efforts. The research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation, as well as validation using triangulation. The results show that teachers have understood the 4C principles and tried to apply them through active learning models such as Problem Based Learning (PBL) and simple projects. However, implementation is still limited by the constraints of technology facilities, teachers' ICT skills, and the limitations of operational indicators in the lesson plan and assessment rubric. Nevertheless, authentic assessments in the form of projects and portfolios began to be implemented and received a positive response from students. This research emphasizes the importance of teacher training support, strengthening ICT facilities, and consistency in the application of assessment rubrics so that innovative learning in the 21st century can run optimally in elementary schools.